Exploring PAI Students' Critical Thinking Competencies for Seizing Society 5.0 Era Opportunities Using Mixed-Methods Study - Muhammad Idris; Nelfa Sari; Tria Dian Ramadhayanti; Yesi Ramadhanti (Ta'dib, 2026)
Critical thinking is a key competency for navigating the Society 5.0 era. In reality, the critical thinking abilities of Islamic Education students still vary across various aspects. This study aims to explore the level of critical thinking, identify development efforts, and analyze the obstacles encountered. The study employed a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through a questionnaire administered to 105 sixth-semester students and analyzed using descriptive statistics. Qualitative data were gathered through in-depth interviews and documentation, then analyzed through the stages of data collection, data reduction, data display, and conclusion and verification. The results indicate that students’ critical thinking skills fall into the high category at 82.24%. All aspects of critical thinking achieved high levels. Development efforts include the application of critical thinking in learning, the use of student-centered models and strategies, the utilization of learning technology, and HOTS-based assessment. The challenges identified included differences in students’ initial abilities, time constraints, a learning approach that remains rote-memorization-oriented, low self-confidence, limited facilities and infrastructure, and a lack of training for instructors. The study concluded that PAI students’ critical thinking skills are generally good but still vary and require further development. Unlike previous studies that measured these skills through experimental treatments, this study did not examine the factors causing such variations. These findings should be taken into consideration by faculty members and the department to improve the quality of instruction so that students’ critical thinking skills can develop more optimally.